To whom it may concern: - Yeoman, Steven K. (Kansas State University, 2020)
There is no shortage of literature on the subject of reform in education. Much has been written too about the work of the principal, particularly as it relates to school improvement, the establishment of a strong school culture, and their relationship with teachers. If there is a gap in the literature, it is hearing the voice of those charged with carrying out this important work. Borrowing from Ronai’s (1995) “layered account” autoethnographic approach, this research endeavors to provide voice to the important work of the building principal. Specific attention will be paid to the establishment of a working school partnership (Knight, 2011) and how trust in schools remains a critical pursuit for any educational undertaking. Social capital theory provides the foundation and context for the research study.
Keywords: Principal; Teacher; Partnership; Education